Pengaruh Waktu Sintering Dengan Variasi 60, 90, Dan 120 Menit Dengan Suhu 250°C Pada Pembuatan Brakepad Dengan Matrik Phenolic Resin - Prasetyo, Totok Susilo (2016)
Brake is one component of a motor vehicle which serves to stop the vehicle speed motorcycle. When the rate of high-speed vehicle brake has an important role, even the safety of the rider depends on the quality of the brake lining The aim of this study was to compare the brake with the time variation of sintering to canvass the market for the brand Indopart. Researchers will conduct research begins with making canvass sintering time varies with materials such as fiberglass, aluminum powder, brass powder, graphite, calcium carbonate, barium sulfate, and phenolic resin. After that mix the brake lining material in accordance with a predetermined composition. Then given the pressure while heated (sintering) with a load of 7.5 tons for 7 minutes with a variation of sintering time of 60 minutes, 90 minutes and 120 minutes, with a temperature of 250ºC. Then tested friction with a load of 15 kg for 60 minutes with dry test, spraying of water, with a standard testing SNI 09-2663-1992 then calculated wear and coefficient geseknya, and tested by using a Durometer hardness. From the research that the average wear of the brake lining Indopart lower and better than the brake with the sintering time variation in the friction test for 60 minutes. The coefficient of friction brake Indopart higher than the brake with the variation of sintering time on tests of friction for 60 minutes, the coefficient of friction Indopart high of 0.6708 while approaching at 0.6357 on the brake with a variation of 60 minutes at a temperature of 250 ° C on a test dry , Hardness values Indopart brake better than the brake with the variation of sintering time was 94 shored up, while the value of hardness approaching the brake with the variation of sintering time of 60 minutes dengn sintering temperature of 250 ° C for 88 shored Keywords: brake, sintering time, swipe test, hardness